The Role of Housing Costs in Central Banks’ Inflation Targeting Regimes: The Cases of the Reserve Bank of Australia and the Bank of England - Mark Stephens (Critical Housing Analysis)
Since the 1990s it has become common for central banks to be charged with using interest rates to meet consumer price inflation (CPI) targets. This article examines the cases of the Reserve Bank of Australia (RBA) and the Bank of England (BoE) and finds that whereas the RBA’s CPI target includes a housing cost element, the BoE’s does not. Moreover, it finds that contrasting treatments of housing costs produce different results, depending on whether the index includes mortgage interest as a housing cost. Whilst central banks dislike CPIs that include an element of mortgage interest because of the apparently perverse outcome of increasing interest rates, they also lack credibility by excluding such an important element of the cost of living. Credibility demands that the 30-year consensus on inflation targeting by monetary policy be replaced by a broader set of tools – including fiscal policy – to control inflation.